Contrasting nonclassical silicon-hydrogen interactions in niobium and tantalum half-sandwich complexes: Si-H center dot center dot center dot M agostic versus M-H center dot center dot center dot Si-Cl interligand hypervalent interactions - Nikonov, G; Mountford, P; Green, J; Cooke, P; Leech, M; Blake, A; Howard, J; Lemenovskii, D (2000)
Reaction of [CpM(NAr)(PMe3)2] (M = Nb, Ta; Ar = 2,6-C6H3iPr2) with HSiClMe2 gives two remarkably different nonclassical Si···H···M products depending only on the identity of M; [CpTa(NAr)(H)(SiMe2Cl)(PMe3)] possesses an unusual electron-rich M-H···Si interligand hypervalent interaction while [CpNb{η3-N(Ar)SiMe2-H}Cl(PMe3)] is the first example of a β-agostic silylamine Si-H···M interaction showing a 'stretched' Si-H bond.